Innovation Affects the Structure of Organizations - Benalcázar-Ordóñez, Freddy Javier (2019)
Innovation is strongly identified with “changes” and “creativity” to do new things, causing to transform and affect any type of industries and/ or companies, therefore it is essential that organizations improve their business model by applying innovation as part of their strategies, not only to create or improve a product but also to change their structure, and thus increase their change of success. The work collected important literature on the types of innovation, change process (Lewin Model), Follow-up model to be able to understand the need to face changes and the importance of transforming and avoid to losing positions in the market. Finally, the Ecuadorian company Válvulas del Pacifico Pacifvalvs S.A was analyzed to which it is immersed in the oil industry to observe the changes it has undergone since it started its operations 9 years ago and which were its innovations to continue being productive and profitable.